On the parameters of geometric constraints for cracked plates under tension - three-dimensional problems - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides a comparative analysis of selected parameters of the geometric constraints for cracked plates subjected to tension. The results of three-dimensional numerical calculations were used to assess the distribution of these parameters around the crack front and their changes along the crack front. The study also involved considering the influence of the external load on the averaged values of the parameters of the geometric constraints as well as the relationship between the material constants and the level of the geometric constraints contributing to the actual fracture toughness for certain geometries.
Keywords: CC(T); DEN(T) and SEN(T) specimens; geometric constraints; stress triaxiality parameter; Q stresses; normal stresses; cracks